Global progress in tobacco control: the question of policy compliance - Anderson, Carrie L.; Mons, Ute; Winkler, Volker (Global health action, 2020)
Background: Currently, about 65% of the world’s population is covered by at least one MPOWER tobacco control policy measure. The impact of such policies might rely on policy compliance. Objective: This study aims to describe and compare global trends in legislation and compliance of the following three tobacco control policies between 2009 and 2019: direct advertisement, promotion and sponsorship, and smoke-free environments. Method: Data from the six most recent WHO Tobacco Control (2009-2019) reports were used to show the development of and possible associations between legislated policies and policy compliance. Data pertaining to the three indicators direct advertisement, promotion and sponsorship, and smoke-free environments were collected and analysed per country income category, according to the Organization for Economic Co-operation and Development. For each country, we (i) calculated the legislation describing the situation according to the law as a percentage of fulfilled MPOWER measurements and (ii) present the level of compliance (ranging from 0 to 10) for the corresponding policy. Results: Both tobacco control policy legislation and compliance for direct advertising improved worldwide - between 2009 and 2019 the median increased from 37.5% to 87.5% for policy and from 5 to 8 for compliance. In contrast, promotion and sponsorship restrictions hardly developed since 2011 and are especially weak among low- and middle-income countries. With respect to smoke-free environments, global policy legislation increased steadily over time while the relative compliance hardly increased. In 2019 data did not show significant correlations between policy legislation and compliance: direct advertising ρ = −0.003, p = 0.970; promotion and sponsorship ρ = 0.140, p = 0.107; smoke-free environments ρ = 0.158, p = 0.070. Conclusion: There is a clear need to understand the barriers in achieving tobacco control policy compliance and to routinely collect and incorporate data on compliance in research in order to generate a more reliable basis for further improvements in tobacco control.
Gesehen am 22.12.2020